(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study examines Indonesia’s challenges in establishing safe and environmentally sound ship recycling practices aligned with national regulations and the Hong Kong Convention. It identifies discrepancies between existing regulations and current industry practices, proposing actionable recommendations for improvement. Study Design/Methodology/Approach: This study used a qualitative approach, conducting a comprehensive literature review. This involved analysing national and international ship recycling regulations and evaluating Indonesian ship recycling practices for compliance with safety and environmental standards. Findings: Significant regulatory gaps persist in Indonesia’s ship recycling industry, leading to widespread non-compliance with international standards. Prevalent hazardous practices, including beaching and inadequate waste management, pose substantial risks to both workers and the environment. Furthermore, deficient infrastructure and weak enforcement exacerbate these issues, underscoring an urgent need for regulatory reform. Originality/Value: This study emphasises the urgency of ship recycling modernisation as part of strengthening Indonesia’s National Resilience through the Astagatra framework, including Geography (maritime territorial protection), Demography (safety of shipyard workers), Natural Resources (hazardous waste and material reuse), as well as the Pancagatra dimensions of ideology, politics, economy, socio-culture, defence, and security. This research offers original insights into Indonesia’s ship recycling sector, highlighting the critical need for facility modernisation, enhanced enforcement, and regulatory alignment with international standards. Future research should investigate the feasibility of green ship recycling technologies and public-private partnerships to advance industry sustainability.